Dampak Gangguan Sistem Imun Terhadap Hematologi Pasien - Enjeli Kurnia Safitri; Latifah Nur Azizah; Luluk Listyowati; Nabila Fatimatu Az-Zahra; Nina Mur Sabekti; Rahmdani Eva Nur Salma; Liss Dyah Dewi Arini (INDO PUBLISHING, 2025)
Immune system disorders can affect hematological functions, potentially leading to blood abnormalities such as anemia, leukopenia, or thrombocytopenia. This study aims to analyze the impact of immune dysfunction on hematological parameters and to improve community knowledge through a community-based educational approach. The research employed a quantitative descriptive design with pre-test and post-test evaluation, involving 45 community participants in Surakarta. The program was conducted over three months through health education sessions, community mentoring, and assessments of knowledge and health behavior. The results showed a significant improvement between pre-test and post-test scores (p < 0.05), with an average knowledge increase of 28.3%. The highest improvement was found in understanding immune disorder prevention (29.5%), while the most notable behavioral changes included regular blood checkups (48%) and increased social support for immunocompromised patients (33%). These findings indicate that community-based education effectively enhances health literacy and awareness of the relationship between the immune and hematological systems. In conclusion, this community engagement program provided not only theoretical insight into immune-hematologic interactions but also tangible improvements in health behavior. It is recommended that similar programs be continued and expanded to improve quality of life and prevent immunological disorders at the community level.